THE ORIGIN OF PROTEIN AND FATTY YOLK IN RANA PIPIENS : II. Electron Microscopical and Cytochemical Observations of Young and Mature Oocytes - Ward, Robert T. (The Rockefeller University Press, 1962)
Electron microscope studies of young oocytes have demonstrated that the plate-like, hexagonally shaped yolk bodies previously observed in living cells are wholly within the substance of oocyte mitochondria and that they remain within these mitochondria while increasing in size. These bodies possess a crystalline structure consisting of what appear to be lines, with a spacing of 70 to 85 A, and appear very dense in the electron microscope. After formalin fixation such bodies give an intense positive test for protein, and when viewed in the electron microscope are only slightly less dense than after OsO(4) fixation. Evidence is presented for the origin of these crystals within a single crista. The clusters of yolk globules previously studied in living cells are seen to consist of several types of bodies, but an irregular dense droplet predominates. This dense material is apparently secreted by small spherical bodies which, the evidence suggests, originate from the breaking up of filamentous mitochondria and which possess an outer double membrane and sometimes internal cristalike membranes. When thin sections of young oocytes are immersed in xylol the dense globules of the clusters are dissolved, but the hexagonal bodies are unaffected, indicating that the globules are of a predominantly fatty nature, while the hexagonal bodies are of a predominantly protein nature. Examination of mature or almost mature oocytes has revealed that the main body of the yolk platelets is crystalline in nature and is surrounded by a thick matrix which, in light microscope study, masks the fact that the face view of the main body of the platelets is often hexagonal. The spacing within the main body is found to be 70 to 85 A. The crystal laminae of this material can be resolved quite clearly into rows of particles. Dense globules of varying sizes are found in the cytoplasm between the platelets. When thin sections of these OsO(4)-fixed oocytes are immersed in xylol, the material of the globules is extracted and the crystalline material of the platelets remains unaffected, indicating the fatty nature of the globules and the protein nature of the platelets. The platelets of the mature egg resemble the hexagon bodies, previously described in young oocytes, in their protein nature, their crystalline spacing, and their hexagonal outline. This is given as strong evidence for the origin of the mature platelets by the growth of the intramitochondrial hexagon bodies. The biochemical implications of this study are discussed.